APPLICATION OF DSC METHOD FOR CANNED MILK PRODUCT IDENTIFICATION - Budanina L.N.; Vereshchagin A.L.; Bychin N.V. (Техника и технология пищевых производств)
In this study, we investigated the possibility of using differential scanning calorimetry to evaluate the samples of canned milk prod-ucts with a mass fraction of milk fat up to 20 %. 15 samples of canned dairy products (condensed milk, sterilized milk, cream) sold in the commercial network of the Altai Territory were used as the object of study. A sample of water-free milk fat (melted butter ofindividual production) was taken for comparison. Based on these studies, the following conclusions have been made: DSC methodallows us qualitatively identify canned dairy products with a mass fraction of milk fat up to 20 % for the presence of non-dairy fat by identifying of endoeffects within 30-40 °C. Within these limits, the melting temperature of milk fat saturated triglycerides differsfrom that of palm oils by two to three degrees. Average values of melting heats of the triglyceride groups in the studied samples and their melting point have been calculated. For samples of sterilized milk the temperatures of two observed endoeffect maximums were close to the melting points of milk and final melting temperature of milk fat, and the magnitude of these thermal effects differ signifi- cantly from the enthalpy of melting ice and water-free milk fat. The addition of sugar results in decrease of samples melting temperature. At the same time, the magnitude of these effects is substantially less than the fusion enthalpy of ice and anhydrous milk fat. Thiscan be explained by different character of intermolecular interaction between the components of milk, vegetable fats and sugar. It has also been found that of the fifteen samples of analyzed canned milk products twelve ones contain non-dairy fats, and only five samples have information about vegetable fats available.